Frequency of Vitamin D Deficiency in Patients with Acute ST Elevation MI - Syed Ikramullah, Aamna Khokhar, Muhammad Usman Ali, Bilal Mustafa, Syed Ahsan Raza, Iftikhar Ahmad (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Vitamin D deficiency in individuals with acute ST Elevation is the goal of this study. Stud Design: Case control/Prospective study Place and Duration: Conducted at Islamabad medical and dental college, Islamabad. Duration was six months from 1st July, 2021 to 31st Dec, 2021. Methods: There were one hundred and six patients were presented in this study. ACS patients were included if they had ST elevation myocardial infarction (STEMI) or not if they had non-STEMI. Informed permission was obtained prior to obtaining demographic data on the enrolled patients. These demographics included age, sex, BMI, and any co-morbidities they may have. Patients were divided in two groups, group I had 53 patients had ST elevation myocardial infarction (STEMI) and group B had 53 patients without STEMI. Frequency of vitamin deficiency among both groups were assessed and compared. SPSS 24.0 was used to analyze complete data. Results: There were majority males 68 (64.2%) and 38 (35.8%) females among all patients. Mean age of the patients was 56.8±11.53 years with mean BMI 27.12±14.43 kg/m2 in group I and in group II mean age was 54.13±6.23 years and had mean BMI 25.7±10.51 kg/m2. Hypertension, diabetes mellitus, myocardial infarction and dyslipidemia were the commonest comorbidities found among all cases. Frequency of vitamin D deficiency in group I was higher found in 42 (79.2%) cases as compared to group II found in 22 (41.5%) cases with p value <0.004.Frequency of vitamin D insufficiency was also higher in patients with STEMI. Conclusion: Vitamin D deficiency and insufficiency were shown to be more common in individuals with acute coronary syndrome, including ST-elevation myocardial infarction (STEMI). People with ACS who had a vitamin D deficit were more likely to have an ST-elevation myocardial infarction (MI). Keywords:Acute coronary syndrome, ST elevation myocardial infarction (STEMI), Vitamin D Deficiency, Comorbidities